Independent effects of exercise intensity on hepatic fat reduction in adults with metabolic dysfunction–associated steatotic liver disease: a randomized controlled trial protocol - Huang, Wei; He, Yifei; Chen, Rong; Huo, Cuilan; Xie, Yijun; Lin, Yanyu; Wang, Tian; Dai, Xiangdi; Wang, Junyu; Ruan, Weiqi; Zhai, Haonan; Zhuang, Jie; et al. (Frontiers in Endocrinology, 2026)
ImportanceExercise is considered a cornerstone of Metabolic dysfunction–associated steatotic liver disease (MASLD) management, but the independent role of exercise intensity in hepatic fat reduction has not been fully elucidated in clinical practice. The primary objective in this study is to evaluate the difference in exercise-induced reduction of hepatic fat content (HFC) between energy-matched high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT). Furthermore, this study aims to investigate whether high-intensity exercise with lower exercise volume can yield comparable HFC reductions to moderate-intensity continuous training.MethodsThis single-center, three-arm, open-label randomized controlled trial will recruit 105 adults aged 18–45 years with MASLD. Participants will be randomized in a 1:1:1 ratio to HIIT, MICT, or a low-volume HIIT (LHIIT). The sample size of 35 participants per group was calculated to provide 90% power to detect a significant difference in HFC reduction between the HIIT and MICT groups (two-sided α = 0.05, accounting for 20% dropout). The supervised exercise training will be conducted at a community fitness center for 12 weeks. The primary outcome is the absolute change in HFC, measured by magnetic resonance imaging–proton density fat fraction. Secondary outcomes include anthropometric parameters, abdominal adipose tissue, body composition, cardiometabolic biomarkers, and cardiorespiratory fitness. The analysis of the primary and secondary outcomes will be conducted according to the intention-to-treat principle.DiscussionThis trial rigorously evaluates the independent effect of exercise intensity on HFC under energy-matched conditions, while simultaneously exploring the therapeutic efficiency of low-volume interventions. The findings of this study are expected to provide a theoretical and practical basis for precise exercise prescriptions for the MASLD population. The results will be disseminated through a peer-reviewed journal.Clinical Trial Registrationhttps://www.chictr.org.cn/showprojEN.html?proj=279678, identifier ChiCTR2500107821.